2000
DOI: 10.1182/blood.v95.9.2806.009k01_2806_2812
|View full text |Cite
|
Sign up to set email alerts
|

Generation of T cells from adult human hematopoietic stem cells and progenitors in a fetal thymic organ culture system: stimulation by tumor necrosis factor-α

Abstract: To investigate the T-lymphopoietic capacity of human adult bone marrow (ABM) hematopoietic progenitor cells, CD34+Lin−, CD34+CD38+, and CD34++CD38− cells were cultured in a severe combined immunodeficient (SCID) mouse fetal thymic organ culture (FTOC). Direct seeding of these progenitors resulted in a moderate to severe cell loss, particularly for the CD34++CD38− cell fraction, and T cells could only be generated from the CD34+Lin− fraction. Preincubation for 36 hours with interleukin-3 (IL-3) and stem cell fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…Zuniga‐Pflucker et al [24] have shown that TNF is important for the induction of critical events leading to murine T‐lineage commitment and maturation in a thymus reconstitution assay, acting either directly on lymphocyte precursors or indirectly on a non–T cell subset that is critical for T‐cell maturation. In line with these findings in mice, Weekx et al [25] showed that, in the in vitro FTOC system, TNF promotes T cell differentiation of CD34 + cells from adult human BM, which we have also observed for human CB‐derived CD34 + cells (our unpublished data). Of interest, genetic polymorphism leading to increased TNFα production may enhance susceptibility to adult T‐cell leukemia/lymphoma among human T‐lymphotropic virus I carriers [34].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Zuniga‐Pflucker et al [24] have shown that TNF is important for the induction of critical events leading to murine T‐lineage commitment and maturation in a thymus reconstitution assay, acting either directly on lymphocyte precursors or indirectly on a non–T cell subset that is critical for T‐cell maturation. In line with these findings in mice, Weekx et al [25] showed that, in the in vitro FTOC system, TNF promotes T cell differentiation of CD34 + cells from adult human BM, which we have also observed for human CB‐derived CD34 + cells (our unpublished data). Of interest, genetic polymorphism leading to increased TNFα production may enhance susceptibility to adult T‐cell leukemia/lymphoma among human T‐lymphotropic virus I carriers [34].…”
Section: Discussionsupporting
confidence: 90%
“…In mice, TNF induces CD25 (IL‐2R) expression on early immature thymocytes and is required for additional thymocyte maturation to single‐positive (SP) CD4 and CD8 cells [24]. Weekx et al [25] showed that TNF also promotes differentiation of human BM CD34 + ‐enriched cell populations into T cells in the FTOC system. However, T‐cell differentiation and selection, as well as the thymus architecture, are normal in TNF knockout mice.…”
Section: Introductionmentioning
confidence: 99%
“…Higher proliferative capacity of CFU-GM, BFU-E, CFU-GEMM; greater proportion of CD38 ) CD34 + cells* (Broxmeyer et al, , 1992Mayani et al, 1998;Nakahata & Ogawa, 1982) Superior engraftment of CB CD34 + cells in NOD/SCID mice* , (Larochelle et al, 1996;Noort et al, 2001;Wang et al, 1997) Superior migration of CB CD34 + cells* , (Voermans et al, 1999) Superior generation of B and T-lymphocyte progenitors* (Arakawa-Hoyt et al, 1999;Weekx et al, 2000) Immunological 'immaturity'* , : -lower numbers of CD4 + , CD8 + and CD3 + T-cells and higher CD4/CD8 ratio -higher proportion of naïve CD45RA + T-cells -lower Th-1 type cytokines, eg IFN-c and TNF-a -reduced capacity of dendritic cells to produce IL-12 -immature T cell gene expression profile -greater T cell receptor diversity (Bradley & Cairo, 2005;Chang et al, 2005;Goriely et al, 2001;Harris et al, 1992;Kaminski et al, 2003;Nomura et al, 2001;Rabian-Herzog et al, 1993;Risdon et al, 1995;Talvensaari et al, 2002) NK-cells with higher cytotoxic activity (Gardiner et al, 1998;Nomura et al, 2001;Rabian-Herzog et al, 1993) biological and clinical significance of these findings, particularly for regenerative medicine, is yet to be fully defined [reviewed in and (Riordan et al, 2007)] and is not further considered in this review.…”
Section: Characteristics Referencesmentioning
confidence: 99%
“…Common lymphoid progenitors mature towards B-, T-, natural killer and dendritic cells [6,7]. T-cell development involves a complex process beginning from common lymphoid progenitor to mature pro-T-cells, followed by maturation and selection mainly in the thymus [8][9][10].…”
Section: Bone Marrow Biologymentioning
confidence: 99%